P257 Human Cytomegalovirus Binding to Neutrophils Triggers a Pro-Survival Secretome That Modulates Monocyte Migration, Activation and Phenotype. (19th November 2012) - Reaves, M; Storisteanu, D; Wills, M; Chilvers, ER; Cowburn, AS
Abstract : Neutrophils provide the body's first line of defence against invading pathogens. They respond to infection by releasing an array of chemokines, cytokines, and superoxide anions that initiate cascades of other immune mediators and cell types. Although the rapid response and flexibility of neutrophils make them an integral part of the body's immune system, human cytomegalovirus (HCMV), paradoxically, may use neutrophil activation for its own evolutionary advantage. Here we report that human peripheral blood neutrophils exposed to a clinical strain of HCMV display a profound survival phenotype that occurs independent of viral gene expression. The initial HCMV driven survival response was partially dependent on ERK1/2 activation and profoundly inhibited by inhibition of NF-kB. Intriguingly, this initial survival event triggered by virus binding was augmented by a cytokine mediated effect whereby supernatants from infected neutrophils provided uninfected neutrophils with substantial protection against apoptosis – a protection which was PI3K as well as ERK1/2 and NF-kB dependent. Concomitant with a transferable survival effect the HCMV-neutrophil secretome also markedly manipulated autologous donor monocytes. Enhanced migration and subsequent differentiation to a permissive phenotype for HCMV infection was suggestive of a mechanism for efficient viral dissemination from the site of initial infection. Fascinatingly, although differentiation to a permissive phenotype was observed this was concomitant with down-regulation of a number of key activators of the adaptive immune response. Overall, these data illustrate the manipulation of an anti-viral response by a pathogen to enhance the outcome of infection which, intriguingly, involves a cell type not productively infected by the pathogen itself. These data further illustrate the complexity of pathogen interactions with the host immune system as well as providing new clues into the mechanisms HCMV exploits for efficient viral dissemination which could have implications on our understanding for HCMV pathogenesis.